2008
DOI: 10.1027/1618-3169.55.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Modulations of Valence Processing in the Emotional Stroop Task

Abstract: This study investigated trial-to-trial modulations of the processing of irrelevant valence information. Participants (N = 126) responded to the frame color of pictures with positive, neutral, or negative affective content--a procedure known as an emotional Stroop task (EST). As is typically found, positive and negative pictures delayed responses as compared to neutral pictures. However, the type and extent of this valence-based interference depended on the irrelevant picture valence in the preceding trial. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 21 publications
4
21
2
1
Order By: Relevance
“…We found neither a general increase of RTs right after negative stimuli (McKenna & Sharma, 2004) nor a more detrimental impact of subsequent negative stimuli (Kunde & Mauer, 2008). The reasons for this are not entirely clear.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…We found neither a general increase of RTs right after negative stimuli (McKenna & Sharma, 2004) nor a more detrimental impact of subsequent negative stimuli (Kunde & Mauer, 2008). The reasons for this are not entirely clear.…”
Section: Discussioncontrasting
confidence: 39%
“…For example, Kunde and Mauer (2008) studied adaptations to valence-based interruption. They observed that interruption effects increased when the preceding trial contained valent information, relative to when it did not.…”
Section: Valence-based Interruption and Interferencementioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that state congruent stimuli exert less interference than state incongruent ones. Although contrary to original expectations and emotionally focused Stroop tasks, these emergent findings are consistent with recent work by Kunde and Mauer (2008) who posited that greater cognitive effort is required to process incongruent valence stimuli, similar to the original Stroop effect, thus resulting in greater response latency (Botvinick, Braver, Barch, Carter, & Cohen, 2001;Kunde & Wuhr, 2006;Stroop, 1935). Allocating attentional resources to mood incongruent information might be functional for the regulation of emotion and action which is important for mood repair (Taylor, 1991), and, crucially in an RT context, for flexible switching of attention between opportunities for enhancing well-being to allow the individual to allocate sufficient attention to new goals (Rothermund, 2003).…”
Section: Study 1 Discussionsupporting
confidence: 81%
“…One approach (e.g., Kunde & Mauer, 2008) posits that greater cognitive effort is required to process incongruent stimuli; thus, attending to words of opposite valence to the current motivational state would exert greater disruption and interference, increasing response latency. The theorized 'confusion' or enhanced processing that results from an incongruent stimulus is somewhat consistent with paradigms advocating that threatening stimuli affect attentional disengagement, effectively 'capturing' an individual's attention for longer before they can attend to a secondary stimulus (e.g., Fox, Russo, Bowles, & Dutton, 2001).…”
mentioning
confidence: 99%